Cardiac manifestations of sarcoidosis - Anna Gorajek; Małgorzata Kudan; Karolina Mikut (Kazimierz Wielki University, 2022)
Introduction and purpose: Sarcoidosis is a chronic, multi-system inflammatory disorder of unknown etiology. Due to the varied clinical picture of patients, the diagnosis of the disease is complicated, especially when the heart is affected.The aim of this article is to review the available diagnostic tools used for the diagnosis, evaluation and monitoring of patients with suspected cardiac sarcoidosis. Description of the state of knowledge: Sarcoidosis may affect any organ, but in particular lungs, skin, lymph nodes, eyes, liver and spleen. The most common manifestations are persistent cough, skin changes, visual disturbances, peripheral lymphadenopathy, fatigue and incidental abnormal chest radiograph. Cardiac sarcoidosis, occurring in about 5% of patients, is clinically significant with a wide range of symptoms including conduction abnormalities, ventricular arrhythmias, heart failure and sudden death. The diagnosis of cardiac sarcoidosis is challenging and often requires a combined approach using clinical data and advanced imaging. Invasive and non-invasive diagnostic tests are helpful in assessing the severity of heart involvement, with non-invasive tests becoming increasingly important, due to low sensitivity (30%) and high complication rate of endomyocardial biopsy for the diagnosis of cardiac sarcoidosis. Summary: Sarcoidosis significantly increases the mortality of patients and furthermore causes impaired quality of life and disability. Attempts to accurately assess the development of disease provide a more comprehensive and personalized care for patients. Especially cardiac sarcoidosis, as a potentially life-threatening localization, requires early diagnosis and appropriate treatment.